Hydrogenated resin product as well as preparation method and application thereof

By reacting the polymerization and hydrogenation of the carbon nine fraction of ethylene cracking with bio-based olefins, bio-type hydrogenation resin products were prepared, which solved the problems of shortage of petroleum resources and poor temperature resistance of adhesives, achieved higher adhesion and durability, and promoted sustainable development.

CN119751757APending Publication Date: 2025-04-04HENGHE MATERIALS & SCI TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411822431.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-11
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

The problem of shortage of petroleum resources and poor temperature resistance of adhesives produced by petroleum-based products in the prior art.

Method used

Bio-type hydrogenation resin product was prepared by distilling the ethylene cracking carbon nine fraction and mixing it with bio-based olefins, conducting radical polymerization and hydrogenation reaction.

Benefits of technology

It improves the adhesion and durability of adhesives, reduces dependence on petroleum resources, and reduces carbon emissions, which is in line with the trend of sustainable development.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005183402820000091
    Figure BDA0005183402820000091
  • Figure BDA0005183402820000101
    Figure BDA0005183402820000101
  • Figure BDA0005183402820000111
    Figure BDA0005183402820000111
Patent Text Reader

Abstract

The invention discloses a hydrogenated resin product as well as a preparation method and application thereof, and relates to the technical field of petrochemical industry. The invention discloses a preparation method of a hydrogenated resin product, which comprises the following steps: rectifying an ethylene cracking C9 fraction to obtain a cracking C9 raw material with a distillation range of 150-200 DEG C; the method comprises the following steps: mixing a cracked C9 raw material with bio-based olefin, and carrying out free radical polymerization to obtain a polymerized resin liquid; and removing the solvent to obtain the biological C9 thermal polymerization petroleum resin. Diluting the biological C9 thermal polymerization petroleum resin with a saturated solvent, and filtering to obtain a biological C9 thermal polymerization petroleum resin liquid; and finally, carrying out hydrogenation reaction to obtain a hydrogenated resin product. The biological hydrogenated C9 petroleum resin and the biological hydrogenated liquid resin separated from the hydrogenated resin product can be applied to products such as hot melt adhesives and pressure-sensitive adhesives, and have an excellent effect on improving the temperature resistance of the hot melt adhesives and the pressure-sensitive adhesives.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of petrochemical industry, and in particular to a hydrogenated resin product and a preparation method and application thereof. Background Art

[0002] Pressure-sensitive adhesives, commonly used in labels, packaging and medical patches, rely heavily on petroleum-based tackifying resins and softeners for their performance. Hot melt adhesives, used for sealing and bonding metals, plastics and other materials, especially in the automotive, construction and electronics sectors, are affected by petroleum resins for their viscosity and heat resistance. Petroleum resins, including fractions such as C5 and C9, are obtained through different polymerization and modification processes and are the key components in these adhesives to provide the necessary adhesion and durability.

[0003] However, as the global demand for oil continues to grow, resource depletion and price fluctuations have become challenges that cannot be ignored, which directly affects the cost of adhesives and the stability of the supply chain. At the same time, the use of petroleum-based products has exacerbated carbon emissions and ecological damage, running counter to the current global trend of green and sustainable development. In addition, the existing pressure-sensitive adhesives or hot-melt adhesives have poor temperature resistance, which narrows their application range. Summary of the invention

[0004] The main purpose of the present invention is to provide a hydrogenated resin product and a preparation method and application thereof, so as to solve the problem of shortage of petroleum resources and poor temperature resistance of adhesives made from petroleum-based products in the prior art.

[0005] In order to solve the above technical problems, according to a first aspect of the present invention, a method for preparing a hydrogenated resin product is provided, comprising the following steps:

[0006] S1, distilling the ethylene cracking carbon nine fraction to obtain a cracking carbon nine raw material with a distillation range of 150 to 200° C.;

[0007] S2, mixing the cracked carbon nine raw material with the bio-based olefin to obtain a composite; in the composite, the mass fraction of the cracked carbon nine raw material is greater than or equal to 70% and less than 100%, and the mass fraction of the bio-based olefin is greater than 0 and less than or equal to 30%;

[0008] S3, subjecting the compound to free radical polymerization to obtain a polymerized resin solution;

[0009] S4, removing unpolymerized components and oligomers in the polymerized resin liquid to obtain a bio-based carbon nine thermally polymerized petroleum resin;

[0010] S5, diluting the bio-based carbon nine thermally polymerized petroleum resin with a saturated solvent, filtering, and obtaining a bio-based carbon nine thermally polymerized petroleum resin liquid;

[0011] S6, hydrogenating the bio-type carbon nine thermally polymerized petroleum resin liquid to obtain a hydrogenated resin product.

[0012] Furthermore, in S1, the distillation method is: adding the ethylene cracking carbon nine fraction into a flash tower, and flashing at a bottom temperature of 150 to 200° C. and a vacuum degree of -0.09 to -0.095 MPa.

[0013] Furthermore, in S1, the total mass fraction of naphthalene, methylnaphthalene and dimethylnaphthalene in the cracking carbon nine raw material is less than 3%.

[0014] Further, in S2, the bio-based olefin is at least one of α-pinene, β-pinene, limonene, phellandrene, myrcene, cedrene, caryophyllene, longifolene, and santalene.

[0015] Furthermore, in S2, in the composite, the mass fraction of the cracked carbon nine raw material is greater than or equal to 75% and less than 95%, and the mass fraction of the bio-based olefin is greater than 5% and less than or equal to 25%.

[0016] Furthermore, in S3, the conditions of free radical polymerization are: polymerization temperature 200-270° C., and polymerization time 10-60 h.

[0017] Furthermore, in S4, the solvent is removed at 180 to 200° C. and -0.08 to -0.085 MPa, and the oligomer is removed at 200 to 240° C. and -0.09 to -0.095 MPa.

[0018] Furthermore, in S5, the saturated solvent is at least one of C8-C12 cycloalkanes and C8-C12 straight-chain alkanes.

[0019] Furthermore, in S5, the mass ratio of the bio-based carbon nine thermally polymerized petroleum resin to the saturated solvent is 1:(8-12).

[0020] Furthermore, in S6, the temperature of the hydrogenation reaction is 200-270°C, the hydrogen pressure is 13-25 MPa, and the space velocity is 0.15-0.55 h -1 , the hydrogen-oil ratio is (500~1000):1.

[0021] Furthermore, in S6, the hydrogenation reaction is carried out in a fixed bed hydrogenation reactor, which has four layers, wherein the upper two layers are loaded with a Pd / Ni / C composite catalyst, and the Pd / Ni / C composite catalyst is supported by Al2O3; taking the mass fraction of the Pd / Ni / C composite catalyst as 100%, the mass fraction of Pd is 0.5% to 1.5%, the mass fraction of Ni is 8% to 12%, and the molar ratio of C to Al2O3 is 1:(1 to 2); the specific surface area of ​​the Pd / Ni / C composite catalyst is 70 to 150 m 2 / g, average particle size is 2-6mm, bulk density is 550-750kg / m 3 ;

[0022] The lower two layers are loaded with Pd / Ni composite catalyst, which uses Al2O3 as a carrier; based on the mass fraction of the Pd / Ni composite catalyst being 100%, the mass fraction of Pd is 0.5% to 1.5%, and the mass fraction of Ni is 10% to 15%; the specific surface area of ​​the Pd / Ni composite catalyst is 70 to 150 m 2 / g, average particle size is 2-6mm, bulk density is 650-880kg / m 3 .

[0023] According to a second aspect of the present invention, there is provided a bio-type hydrogenated carbon nine petroleum resin, which is obtained by separating the hydrogenated resin product according to the first aspect of the present invention, and the separation method comprises:

[0024] S1, removing the first solvent in the hydrogenated resin product at 180-200° C. and -0.08--0.085 MPa to obtain a first residual product;

[0025] S2, cutting the first residual product at 200-250° C. and -0.09-0.095 MPa to obtain hydrogenated oligomers and bio-type hydrogenated C9 petroleum resin.

[0026] According to the third aspect of the present invention, a hot melt adhesive is provided, which comprises the following ingredients in parts by weight: 30 to 50 parts of SIS thermoplastic elastomer, 20 to 40 parts of bio-based hydrogenated carbon nine petroleum resin, 2 to 5 parts of pure aromatic resin, 15 to 25 parts of softener, and 0.3 to 1 part of antioxidant; wherein the bio-based hydrogenated carbon nine petroleum resin is the bio-based hydrogenated carbon nine petroleum resin described in the second aspect of the present invention.

[0027] Furthermore, the SIS thermoplastic elastomer has a linear structure, wherein the mass fraction of styrene is 13% to 17%, and the melt index measured at 200° C. and 5 kg is 10 to 20 g / 10 min.

[0028] Furthermore, the pure aromatic hydrocarbon resin is α-methylstyrene / p-vinyltoluene copolymer resin.

[0029] Furthermore, the softener is at least one of hydrogenated naphthenic oil, dioctyl phthalate and paraffin.

[0030] Furthermore, the antioxidant is at least one of a phosphite antioxidant and a hindered phenol antioxidant.

[0031] According to a fourth aspect of the present invention, there is provided a bio-type hydrogenated liquid resin obtained by separating the hydrogenated resin product according to the first aspect of the present invention, the separation method comprising:

[0032] S1, removing the first solvent in the hydrogenated resin product at 180-200° C. and -0.08--0.085 MPa to obtain a first residual product;

[0033] S2, cutting the first residual product at 200-250° C. and -0.09--0.095 MPa to obtain hydrogenated oligomers and bio-type hydrogenated carbon nine petroleum resin;

[0034] S3, removing the second solvent in the hydrogenated oligomer at 230-250° C. and -0.09-0.095 MPa to obtain a bio-type hydrogenated liquid resin.

[0035] According to the fifth aspect of the present invention, a pressure-sensitive adhesive is provided, which comprises the following ingredients in parts by weight: 15 to 25 parts of SIS thermoplastic elastomer, 10 to 20 parts of SIBS thermoplastic elastomer, 10 to 20 parts of a first tackifying resin, 10 to 20 parts of a second tackifying resin, 15 to 25 parts of a bio-type hydrogenated liquid resin, 10 to 15 parts of a softener, and 0.3 to 1 part of an antioxidant; wherein the first tackifying resin is a styrene-modified terpene resin, and the second tackifying resin is a maleic anhydride-grafted styrene-modified C5 petroleum resin; and the bio-type hydrogenated liquid resin is the bio-type hydrogenated liquid resin described in the fourth aspect of the present invention.

[0036] Furthermore, the SIS thermoplastic elastomer has a linear structure, the mass fraction of styrene is 13% to 17%, and the melt index measured at 200° C. and 5 kg is 8 to 12 g / 10 min.

[0037] Furthermore, the mass fraction of styrene in the SIBS thermoplastic elastomer is 18% to 21%, and the melt index measured at 200° C. and 5 kg is 9 to 13 g / 10 min.

[0038] Furthermore, the softener is at least one of hydrogenated naphthenic oil, dibutyl phthalate and paraffin.

[0039] Furthermore, the antioxidant is at least one of a hindered phenol antioxidant and a phosphite antioxidant, and more preferably a hindered phenol antioxidant.

[0040] By applying the technical solution of the present invention, the resin material prepared by polymerizing bio-based olefins and petroleum cracking products can be supplemented by sustainable agricultural and forestry materials, thereby reducing dependence on limited petroleum resources. The introduction of biological components significantly reduces the carbon footprint of the product, which is in line with the global trend of reducing greenhouse gas emissions and helps to reduce the negative impact on the environment. In addition, the present invention can improve the adhesion and durability of the adhesive made from the hydrogenated resin product by hydrogenating the bio-type thermal polymer resin. DETAILED DESCRIPTION

[0041] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.

[0042] As described in the background of the present invention, the prior art has the problem of shortage of petroleum resources and poor temperature resistance of adhesives made from petroleum resources. In order to solve the above technical problems, in a typical embodiment of the present invention, a method for preparing a hydrogenated resin product is provided, comprising the following steps:

[0043] S1, distilling the ethylene cracking carbon nine fraction to obtain a cracking carbon nine raw material with a distillation range of 150 to 200° C.;

[0044] S2, mixing the cracked carbon nine raw material with the bio-based olefin to obtain a composite; in the composite, the mass fraction of the cracked carbon nine raw material is greater than or equal to 70% and less than 100%, and the mass fraction of the bio-based olefin is greater than 0 and less than or equal to 30%;

[0045] S3, subjecting the compound to free radical polymerization to obtain a polymerized resin solution;

[0046] S4, removing unpolymerized components and oligomers in the polymerized resin liquid to obtain a bio-based carbon nine thermally polymerized petroleum resin;

[0047] S5, diluting the bio-based carbon nine thermally polymerized petroleum resin with a saturated solvent, filtering, and obtaining a bio-based carbon nine thermally polymerized petroleum resin liquid;

[0048] S6, hydrogenating the bio-type carbon nine thermally polymerized petroleum resin liquid to obtain a hydrogenated resin product.

[0049] The reason for selecting the cracked carbon nine raw material with a distillation range of 150-200°C to prepare the polymer resin liquid is that the cracked carbon nine fraction in this range contains rich diolefins and monoolefins, which are the key raw materials for preparing high-performance hydrogenated resins. By distilling the carbon nine raw material in this distillation range, high-boiling point components such as naphthalene and its derivatives can be effectively removed. These components may have negative effects in the preparation of resins, such as reducing the thermal stability of the resin or causing the color of the resin to deepen, thereby ensuring the purity and performance of the final hydrogenated resin product. Further, the ethylene cracked carbon nine fraction with a distillation range of 150-250°C is distilled to obtain a cracked carbon nine raw material with a distillation range of 150-200°C. The above-mentioned ethylene cracked carbon nine fraction is rich in components with high activity and polymerization potential such as dicyclopentadiene, indene and its derivatives. These components can form polymers with diverse structures and excellent performance in subsequent polymerization reactions, providing a good foundation for hydrogenated resins.

[0050] The above-mentioned cracked carbon nine raw materials are mixed with bio-based olefins, and the hydrogenated resin products obtained by polymerization and hydrogenation have excellent performance and can reduce the use of fossil fuels. The thermal stability and weather resistance of the resin can be further improved through hydrogenation treatment. This dual improvement gives the resin a wider range of applicability. When it is used in the preparation of adhesives, its temperature resistance can be significantly improved.

[0051] In some embodiments, in S1, the distillation method is: adding the ethylene cracking carbon nine fraction to a flash tower, and flashing at a bottom temperature of 150 to 200° C. and a vacuum degree of -0.09 to -0.095 MPa.

[0052] Under the above conditions, the components can be effectively separated, so that the distillation process can accurately intercept the required fraction and remove unnecessary heavy components, thereby optimizing the component composition of the cracking carbon nine raw material.

[0053] In some embodiments, in S1, the total mass fraction of naphthalene, methylnaphthalene and dimethylnaphthalene in the cracking carbon nine feedstock is less than 3%.

[0054] The above components are likely to cause the generation of by-products in the subsequent polymerization reaction, affecting the color and stability of the resin. Controlling their total mass fraction to less than 3% helps to improve the comprehensive performance of the hydrogenated resin product.

[0055] In some embodiments, in S2, the bio-based olefin is at least one of α-pinene, β-pinene, limonene, phellandrene, myrcene, cedrene, caryophyllene, longifolene, and santalene; preferably at least one of α-pinene and β-pinene.

[0056] Bio-based olefins are derived from renewable biomass resources, such as vegetable oils, gums, and peels. Using them can significantly reduce dependence on fossil resources and reduce CO2 emissions, which is of great significance for responding to global climate change actions and promoting a green economy. In addition, because the supply of bio-based olefins is relatively stable and is not affected by oil price fluctuations, it helps reduce supply chain risks and improve the sustainability and safety of the production process. In addition, the above-mentioned bio-based olefins have unique chemical structures and reactivity, and the obtained hydrogenated resin products can improve their temperature resistance when used in adhesives.

[0057] In some embodiments, in S2, in the composite, the mass fraction of the cracked carbon nine feedstock is greater than or equal to 75% and less than 95%, and the mass fraction of the bio-based olefin is greater than 5% and less than or equal to 25%.

[0058] There are certain differences in chemical structure and reactivity between bio-based olefins and olefin components in cracked carbon nine raw materials. By controlling the ratio of the two, the chemical compatibility can be balanced so that the raw materials can fully react with each other during the polymerization process to form a resin with uniform structure. The adhesive made from the resulting hydrogenated resin product has better temperature resistance and adhesion, and has high economic benefits and a small carbon footprint.

[0059] In some embodiments, in S3, the conditions of free radical polymerization are: polymerization temperature 200-270° C., and polymerization time 10-60 h.

[0060] Under the above conditions, free radical polymerization has a fast reaction rate, which helps to accelerate the polymerization of monomers such as dicyclopentadiene, indene and bio-based olefins, and improve the reaction efficiency; reasonable reaction time ensures the full progress of the reaction, avoids incomplete reaction due to too short a time or excessive polymerization due to too long a time, thereby reducing the risk of by-product formation and improving the yield and purity of the main product.

[0061] In some embodiments, nitrogen is used for replacement 3 to 5 times before the polymerization reaction, and then the compound is added to the autoclave for free radical polymerization. The purity of the reaction product can be improved by using nitrogen replacement.

[0062] In some embodiments, in S4, the solvent is removed at 180 to 200° C. and -0.08 to -0.085 MPa, and the oligomer is removed at 200 to 240° C. and -0.09 to -0.095 MPa.

[0063] Within the above-mentioned temperature and vacuum range, the residual solvents and oligomers in the bio-based carbon nine thermally polymerized petroleum resin can be effectively removed, ensuring that the solvents and oligomers are removed quickly and thoroughly, reducing subsequent processing steps and improving production efficiency.

[0064] In some embodiments, in S5, the saturated solvent is at least one of C8-C12 cycloalkanes and C8-C12 straight-chain alkanes, such as cyclooctane, n-octane, cyclododecane, n-dodecane, etc.

[0065] The above ingredients have good solubility and low volatility, and can effectively dissolve the polymerized bio-type carbon nine thermally polymerized petroleum resin to ensure its uniform dispersion in the subsequent hydrogenation reaction, which helps to improve the hydrogenation efficiency and enable all unsaturated bonds in the resin molecules to be fully hydrogenated, thereby obtaining a hydrogenated resin with consistent performance.

[0066] In some embodiments, in S5, the mass ratio of the bio-based carbon nine thermally polymerized petroleum resin to the saturated solvent is 1:(8-12).

[0067] Under the above conditions, the resin can be completely dissolved in the saturated solvent to form a uniform solution, ensuring the full progress of the hydrogenation reaction, improving the conversion rate and selectivity of the hydrogenation reaction, reducing the generation of by-products, and improving the quality of the resin.

[0068] In some embodiments, in S6, the temperature of the hydrogenation reaction is 200-270°C, the hydrogen pressure is 13-25 MPa, and the space velocity is 0.15-0.55 h -1 , the hydrogen-oil ratio is (500~1000):1.

[0069] Under the above conditions, hydrogen can react quickly and efficiently with the unsaturated bonds in the bio-based carbon nine thermal polymerized petroleum resin, which can enhance the stability of the product.

[0070] In some embodiments, in S6, the hydrogenation reaction is carried out in a fixed bed hydrogenation reactor, which has four layers, wherein the upper two layers are loaded with a Pd / Ni / C composite catalyst, and the Pd / Ni / C composite catalyst is supported by Al2O3; taking the mass fraction of the Pd / Ni / C composite catalyst as 100%, the mass fraction of Pd is 0.5% to 1.5%, the mass fraction of Ni is 8% to 12%, and the molar ratio of C to Al2O3 is 1:(1 to 2); the specific surface area of ​​the Pd / Ni / C composite catalyst is 70 to 150 m 2 / g, average particle size is 2-6mm, bulk density is 650-880kg / m 3 ;

[0071] The lower two layers are loaded with Pd / Ni composite catalyst, which uses Al2O3 as a carrier; based on the mass fraction of the Pd / Ni composite catalyst being 100%, the mass fraction of Pd is 0.5% to 1.5%, and the mass fraction of Ni is 10% to 15%; the specific surface area of ​​the Pd / Ni composite catalyst is 70 to 150 m 2 / g, average particle size is 2-6mm, bulk density is 650-880kg / m 3 .

[0072] The use of layered loaded Pd / Ni / C composite catalysts and Pd / Ni composite catalysts for hydrogenation reactions can not only significantly improve the hydrogenation efficiency and product selectivity, but also optimize the reaction conditions, reduce energy consumption, reduce by-products, and increase the service life of the catalyst and equipment.

[0073] In another typical embodiment of the present invention, a bio-type hydrogenated carbon nine petroleum resin is provided, which is obtained by separating the hydrogenated resin product of the first aspect of the present invention, and the separation method comprises:

[0074] S1, removing the first solvent in the hydrogenated resin product at 180-200° C. and -0.08--0.085 MPa to obtain a first residual product;

[0075] S2, cutting the first residual product at 200-250° C. and -0.09-0.095 MPa to obtain hydrogenated oligomers and bio-type hydrogenated C9 petroleum resin.

[0076] By adopting the above-mentioned method for separation, each component in the hydrogenated resin product can be fully utilized. Among them, the softening point of the separated bio-type hydrogenated carbon nine petroleum resin is 90-140°C, and the yellow index Yi≤10. Applying it to hot melt adhesive can help improve the heat resistance of the hot melt adhesive, provide higher cohesion, and help improve the shock resistance of the hot melt adhesive.

[0077] In another typical embodiment of the present invention, a hot melt adhesive is provided, which includes the following ingredients in parts by weight: 30 to 50 parts of SIS thermoplastic elastomer, 20 to 40 parts of bio-based hydrogenated carbon nine petroleum resin, 2 to 5 parts of pure aromatic resin, 15 to 25 parts of softener, and 0.3 to 1 part of antioxidant; wherein the bio-based hydrogenated carbon nine petroleum resin is the bio-based hydrogenated carbon nine petroleum resin in the above-mentioned embodiment of the present invention.

[0078] By accurately proportioning SIS thermoplastic elastomer, bio-based hydrogenated carbon nine petroleum resin and pure aromatic resin, the optimal balance between the initial adhesion, lasting adhesion and peel strength of the hot melt adhesive can be achieved. The introduction of bio-based hydrogenated carbon nine petroleum resin improves the bonding performance and weather resistance of the hot melt adhesive, especially under extreme temperature conditions. Its excellent cold and high temperature resistance can significantly reduce the risk of cracking under high bumpy roads in automotive adhesive applications.

[0079] In some embodiments, the SIS thermoplastic elastomer is a linear structure, wherein the mass fraction of styrene is 13% to 17%, and the melt index measured at 200°C and 5kg is 10 to 20 g / 10 min, preferably 10 to 14 g / 10 min, such as Kraton D-1161; the pure aromatic resin is α-methylstyrene / p-vinyltoluene copolymer resin, such as Eastman Endex155, Eastman Endex160, etc.; the softener is at least one of hydrogenated cyclohexane oil, dibutyl phthalate, and paraffin, such as Karamay KN-4010 hydrogenated cyclohexane oil, etc.; the antioxidant is at least one of a phosphite antioxidant and a hindered phenol antioxidant, such as antioxidant 1010, antioxidant 168, etc., and the antioxidant is further preferably a compound of a phosphite antioxidant and a hindered phenol antioxidant.

[0080] The hot melt adhesive prepared using the above ingredients has good bonding properties and good stability at high temperatures, thereby improving the overall weather resistance of the hot melt adhesive.

[0081] In some embodiments, the preparation method of the hot melt adhesive is: add SIS thermoplastic elastomer, softener, and part of antioxidant into a vacuum kneader, control the temperature of the vacuum kneader to 150-200°C, preferably 170-180°C, add bio-type hydrogenated carbon nine petroleum resin, pure aromatic resin and remaining antioxidant after kneading evenly, and obtain the hot melt adhesive after kneading evenly.

[0082] In a typical embodiment of the present invention, a bio-type hydrogenated liquid resin is provided, which is obtained by separating the hydrogenated resin product in the above embodiment, and the separation method includes:

[0083] S1, removing the first solvent in the hydrogenated resin product at 180-200° C. and -0.08-0.085 MPa to obtain a first residual product; the first solvent is all substances that can be removed under the above conditions;

[0084] S2, cutting the first residual product at 200-250° C. and -0.09--0.095 MPa to obtain hydrogenated oligomers and bio-type hydrogenated carbon nine petroleum resin;

[0085] S3, removing the second solvent in the hydrogenated oligomer at 230-250° C. and -0.09-0.095 MPa to obtain a bio-type hydrogenated liquid resin; the second solvent is all substances that can be removed under the above conditions.

[0086] When separation is carried out under the above conditions, the resulting bio-based hydrogenated liquid resin has higher purity. Improving the purity is crucial to improving key performance indicators such as the resin's melt viscosity and softening point. The softening point of the bio-based hydrogenated liquid resin obtained by the above separation method is 10±3°C, and the melt viscosity (30°C) is 10000±3000cP. When it is subsequently used to prepare pressure-sensitive adhesives, it exhibits better low-temperature resistance and bonding ability.

[0087] In another typical embodiment, a pressure-sensitive adhesive is provided, which includes the following ingredients in parts by weight: 15 to 25 parts of SIS thermoplastic elastomer, 10 to 20 parts of SIBS thermoplastic elastomer, 10 to 20 parts of a first tackifying resin, 10 to 20 parts of a second tackifying resin, 15 to 25 parts of a bio-type hydrogenated liquid resin, 10 to 15 parts of a softener, and 0.3 to 1 part of an antioxidant; wherein the first tackifying resin is a styrene-modified terpene resin, and the second tackifying resin is a maleic anhydride-grafted styrene-modified C5 petroleum resin; and the bio-type hydrogenated liquid resin is the bio-type hydrogenated liquid resin in the above-mentioned embodiment of the present invention.

[0088] The composite use of SIS thermoplastic elastomer and SIBS thermoplastic elastomer, combined with different tackifying resins, can achieve an excellent balance of initial tack, cohesion, peel strength and viscosity of the pressure-sensitive adhesive. The introduction of bio-type hydrogenated liquid resin, especially in low temperature environment, can significantly improve the adhesion and flexibility of the pressure-sensitive adhesive, which is particularly important in the packaging field of food, beverages, fresh vegetables, etc. that require low temperature storage and transportation. In addition, the second tackifying resin and the bio-type hydrogenated liquid resin can further synergistically improve the weather resistance and chemical stability of the pressure-sensitive adhesive.

[0089] In some embodiments, the SIS thermoplastic elastomer has a linear structure, the mass fraction of styrene is 13% to 17%, and the melt index measured at 200°C and 5kg is 8 to 20g / 10min, such as Yuehua YH-1106; the mass fraction of styrene in the SIBS thermoplastic elastomer is 18% to 21%, and the melt index measured at 200°C and 5kg is 8 to 14g / 10min, such as Kraton D1171; the softener is at least one of hydrogenated cyclohexane oil, dioctyl phthalate, and paraffin, such as Karamay KN-4010 hydrogenated cyclohexane oil; the antioxidant is at least one of hindered phenol antioxidants and phosphite antioxidants, and is further preferably a hindered phenol antioxidant, such as antioxidant 1010; styrene-modified terpene resins such as Kraton 6100, and maleic anhydride-grafted styrene-modified C5 petroleum resins such as Japan Zeon D200.

[0090] The above ingredients help to improve the cohesion and elasticity of the pressure-sensitive adhesive, and improve its fluidity and processing performance; in addition, the prepared pressure-sensitive adhesive has good viscosity and temperature resistance, and performs well at low temperatures; in addition, using the above ingredients to prepare the pressure-sensitive adhesive also reduces the negative impact on the environment.

[0091] In some embodiments, the preparation method of the pressure-sensitive adhesive includes: adding SIS thermoplastic elastomer, SIBS thermoplastic elastomer, softener, and part of antioxidant into a vacuum kneader, the temperature of the kneader is 150-200°C, preferably 170-180°C, after kneading evenly, adding the first tackifying resin, the second tackifying resin, the bio-type hydrogenated liquid resin and the remaining antioxidant, and continuing kneading to obtain the pressure-sensitive adhesive.

[0092] By precisely controlling pre-mixing and post-mixing in a vacuum kneader, combined with optimal raw material selection and preparation conditions, the pressure-sensitive adhesive prepared by the preparation method has good comprehensive properties, such as bonding strength, weather resistance and stability, and also optimizes processing performance and reduces environmental impact.

[0093] The present application is further described in detail below in conjunction with specific embodiments. These embodiments should not be construed as limiting the scope of protection claimed in the present application.

[0094] The material information in the embodiments and comparative examples is as follows:

[0095] The ethylene cracking carbon nine fraction with a distillation range of 150-250°C comes from Zhenhai Refining and Chemical;

[0096] α-pinene and β-pinene were purchased from Jiangxi Huajin New Materials Company;

[0097] Limonene was purchased from Hubei Tosoh Chemical Technology Co., Ltd.;

[0098] Phellandrene was purchased from Wuhan Huaxiang Kejie Biotechnology Co., Ltd.

[0099] Myrcene and caryophyllene were purchased from Hubei Kewode Chemical Co., Ltd.;

[0100] Cedarene was purchased from Hubei Dibai Chemical Co., Ltd.;

[0101] Longifolene was purchased from Wuhan Jixinyibang Biotechnology Co., Ltd.;

[0102] Santalene was purchased from Hubei Langbo Wansheng Biological Co., Ltd.;

[0103] The SIS thermoplastic elastomer used in the hot melt adhesive has a styrene mass fraction of 14% to 17%, a melt index of 10 to 14 g / 10 min measured at 200°C and 5 kg, and is Kraton D-1161;

[0104] The SIS thermoplastic elastomer used in the pressure-sensitive adhesive has a styrene mass fraction of 13% to 17%, and a melt index of 8 to 12 g / 10 min measured at 200°C and 5 kg, Yuehua YH-1106;

[0105] Pure aromatic resin, α-methylstyrene / p-vinyltoluene copolymer resin, Eastman Endex155;

[0106] Softener, hydrogenated naphthenic oil, Karamay KN-4010;

[0107] Antioxidants, antioxidant 1010, antioxidant 168;

[0108] SIBS thermoplastic elastomer, styrene mass fraction is 18-21%, melt index measured at 200℃, 5kg is 9-13g / 10min, Kraton D1171;

[0109] The first tackifying resin, styrene-modified terpene resin, Kraton 6100;

[0110] The second tackifying resin is maleic anhydride grafted styrene modified C5 petroleum resin, Japan Zeon D200.

[0111] The hydrogenation reactor is a fixed bed hydrogenation reactor with four layers. The upper two layers are loaded with Pd / Ni / C composite catalyst, and the Pd / Ni / C composite catalyst uses Al2O3 as a carrier. Taking the mass fraction of the Pd / Ni / C composite catalyst as 100%, the mass fraction of Pd is 1%, the mass fraction of Ni is 10%, and the molar ratio of C to Al2O3 is 1:1.5. The specific surface area of ​​the Pd / Ni / C composite catalyst is 110m 2 / g, average particle size is 4mm, bulk density is 700kg / m 3 ;

[0112] The lower two layers are loaded with Pd / Ni composite catalyst, which is supported by Al2O3. Taking the mass fraction of the Pd / Ni composite catalyst as 100%, the mass fraction of Pd is 1% and the mass fraction of Ni is 13%. The specific surface area of ​​the Pd / Ni composite catalyst is 120m 2 / g, average particle size is 5mm, bulk density is 780kg / m 3 .

[0113]

Hydrogenated resin products

[0114] Example 1

[0115] An embodiment of the preparation method of the hydrogenated resin product of the present invention comprises the following steps:

[0116] S1, adding the ethylene cracking carbon nine fraction into a flash tower, flashing at a bottom temperature of 180°C and a vacuum degree of -0.095MPa, intercepting the fraction with a distillation range of 150-200°C, which is the cracking carbon nine raw material; the components of the ethylene cracking carbon nine fraction and the cracking carbon nine raw material are shown in Table 1:

[0117] Table 1

[0118]

[0119]

[0120] S2, 650 g of cracked carbon nine raw material and 50 g of α-pinene are fully mixed and added into a high-pressure reactor;

[0121] S3, after sealing the kettle, replace it with nitrogen for 3 to 5 times, and add 0.2MPa nitrogen protection, then slowly heat it to 235°C, keep it warm for 40 hours, cool it to room temperature and discharge it to obtain a polymer resin liquid;

[0122] S4, removing the solvent and oligomers from the polymerized resin liquid in a rotary evaporator at a temperature of 200° C. and a vacuum degree of -0.085 MPa and a temperature of 250° C. and a vacuum degree of -0.095 MPa, respectively, to obtain a bio-type carbon nine thermally polymerized petroleum resin;

[0123] S5, mixing the bio-based carbon nine thermally polymerized petroleum resin and n-dodecane at a mass ratio of 1:9 to obtain a diluted solution, and then filtering to obtain a bio-based carbon nine thermally polymerized petroleum resin liquid;

[0124] S6, add the bio-type carbon nine thermally polymerized petroleum resin liquid into the raw material tank of the hydrogenation reactor, and inject the material into the hydrogenation reactor through a metering pump. The hydrogenation temperature is 230°C, the hydrogen pressure is 15MPa, and the space velocity is 0.4h -1 , the hydrogen-to-oil ratio is 800:1, and a hydrogenated resin product is obtained.

[0125] The hydrogenated resin product is separated to prepare bio-type hydrogenated C9 petroleum resin and bio-type hydrogenated liquid resin. The separation method is as follows:

[0126] (1) removing the first solvent from the hydrogenated resin product at 180° C. and −0.095 MPa to obtain a first residual product;

[0127] (2) removing hydrogenated oligomers in the first residual product at 250° C. and −0.095 MPa to obtain a bio-based hydrogenated C9 petroleum resin;

[0128] (3) The heavy solvent in the hydrogenated oligomer was removed at 235°C and -0.095 MPa to obtain a bio-type hydrogenated liquid resin.

[0129] Example 2

[0130] An embodiment of the preparation method of the hydrogenated resin product of the present invention, the preparation method described in this embodiment is different from that in embodiment 1 only in that, in S2, the cracked carbon nine raw material is 600g, and the mass of α-pinene is 100g; in S3, the polymerization temperature is 240°C, and the insulation time is 40h.

[0131] Example 3

[0132] An embodiment of the preparation method of the hydrogenated resin product of the present invention, the preparation method described in this embodiment is different from that in Example 1 only in that, in S2, the cracked carbon nine raw material is 550g, and the mass of α-pinene is 150g; in S3, the polymerization temperature is 245°C, and the insulation time is 40h.

[0133] Example 4

[0134] An embodiment of the preparation method of the hydrogenated resin product of the present invention, the preparation method described in this embodiment is different from that in Example 1 only in that, in S2, the cracked carbon nine raw material is 500g, and the mass of α-pinene is 200g; in S3, the polymerization temperature is 250°C, and the insulation time is 40h.

[0135] Example 5

[0136] An embodiment of the method for preparing the hydrogenated resin product of the present invention, the preparation method described in this embodiment is different from that in embodiment 3 only in that α-pinene is replaced by β-pinene in S2.

[0137] Example 6

[0138] An embodiment of the preparation method of the hydrogenated resin product of the present invention, the preparation method described in this embodiment is different from that in embodiment 1 only in that myrcene is used instead of α-pinene in S2.

[0139] Example 7

[0140] An embodiment of the method for preparing the hydrogenated resin product of the present invention, the preparation method described in this embodiment is different from that in embodiment 1 only in that limonene is used instead of α-pinene in S2.

[0141] Comparative Example 1

[0142] An embodiment of the preparation method of the hydrogenated resin product of the present invention, the preparation method described in this embodiment is different from that in Example 1 only in that, in S2, no α-pinene is added, and the mass of the cracked carbon nine raw material is 700g.

[0143] The performance results of the above examples and comparative examples are shown in Table 2:

[0144] Table 2

[0145]

[0146]

[0147] Examples 8 to 14 and Comparative Example 2

[0148] Examples 8 to 14 and Comparative Example 2 are hot melt adhesives made from the bio-based hydrogenated carbon nine petroleum resins in Examples 1 to 7 and Comparative Example 1, respectively, and are made from the following components in parts by weight:

[0149] SIS thermoplastic elastomer 45 parts, bio-type hydrogenated carbon nine petroleum resin 31.5 parts, pure aromatic resin 3 parts, softener 20 parts, compound antioxidant (the mass ratio of antioxidant 1010 to antioxidant 168 is 4:1) 0.5 parts.

[0150] The preparation method is as follows: add SIS thermoplastic elastomer, softener, and 60% compound antioxidant into a vacuum kneader (NHZ-1L), control the temperature of the vacuum kneader to 170°C, add bio-type hydrogenated carbon nine petroleum resin, pure aromatic resin and remaining antioxidant after being evenly mixed, discharge the material after being completely mixed and bubbles are exhausted, and obtain the hot melt adhesive, and perform performance test on the hot melt adhesive while it is hot.

[0151] Embodiment 15

[0152] The difference between this embodiment and embodiment 8 is that the weight parts of the components in the hot melt adhesive are different, as follows:

[0153] SIS thermoplastic elastomer 50 parts, bio-type hydrogenated carbon nine petroleum resin 30 parts, pure aromatic resin 4.5 parts, softener 15 parts, compound antioxidant (the mass ratio of antioxidant 1010 to antioxidant 168 is 4:1) 0.5 parts.

[0154] Example 16

[0155] The difference between this embodiment and embodiment 8 is that the weight parts of the components in the hot melt adhesive are different, as follows:

[0156] SIS thermoplastic elastomer 32.5 parts, bio-type hydrogenated carbon nine petroleum resin 40 parts, pure aromatic resin 2 parts, softener 25 parts, compound antioxidant (the mass ratio of antioxidant 1010 to antioxidant 168 is 4:1) 0.5 parts.

[0157] Embodiment 17

[0158] The difference between this embodiment and embodiment 8 is that the weight parts of the components in the hot melt adhesive are different, as follows:

[0159] SIS thermoplastic elastomer 27.5 parts, bio-type hydrogenated carbon nine petroleum resin 42 parts, pure aromatic resin 5 parts, softener 25 parts, compound antioxidant (the mass ratio of antioxidant 1010 to antioxidant 168 is 4:1) 0.5 parts.

[0160] Embodiment 18

[0161] The difference between this embodiment and embodiment 8 is that the weight parts of the components in the hot melt adhesive are different, as follows:

[0162] SIS thermoplastic elastomer 53.5 parts, bio-type hydrogenated carbon nine petroleum resin 19 parts, pure aromatic resin 2 parts, softener 25 parts, compound antioxidant (the mass ratio of antioxidant 1010 to antioxidant 168 is 4:1) 0.5 parts.

[0163] The performance of the hot melt adhesive was tested using the following method. The test results are shown in Table 3.

[0164] The initial adhesion test method in the present invention is "GB / T 31125-2014 Ring initial adhesion test method".

[0165] The peel strength test method in the present invention is "GB / T2792-2014 Test method for peel strength of adhesive tape".

[0166] The test method for the holding force in the present invention is "GB / T 4851-2014 Test method for holding force of adhesive tape".

[0167] Table 3

[0168]

[0169]

[0170] Results analysis: (1) As the bio-based groups in the system increase, the performance of the hot melt adhesive improves (Examples 8-10), but when the bio-based groups are too high, the resin performance will decrease as shown in Example 11. Therefore, the addition ratio of bio-based olefins in the compound material is preferably 5% to 25%; (2) By introducing other bio-based groups such as β-pinene, according to the test data in the above table, the application performance of the bio-based hydrogenated resin prepared by introducing β-pinene is similar to that of the product obtained by introducing α-pinene. The product prepared by introducing myrcene has the worst performance, and the product prepared by introducing limonene has better performance than myrcene, but worse than α-pinene and β-pinene; (3) The peel strength of the hot melt adhesive changes with the addition ratio of SIS thermoplastic elastomer. When the addition ratio of SIS thermoplastic elastomer is in the range of 30 to 50 parts, it has both good peel strength and initial adhesion, and has good cold and high temperature resistance.

[0171] Examples 19 to 25 and Comparative Example 3

[0172] Examples 19 to 25 and Comparative Example 3 are pressure-sensitive adhesives made from the bio-type hydrogenated liquid resins in Examples 1 to 7 and Comparative Example 1, and are made from the following components in parts by weight:

[0173] SIS thermoplastic elastomer 20 parts, SIBS thermoplastic elastomer 17 parts, first tackifying resin 13 parts, second tackifying resin 17.5 parts, bio-type hydrogenated liquid resin 19 parts, softener 13 parts, antioxidant 1010 0.5 parts.

[0174] The preparation method is as follows: add SIS thermoplastic elastomer, SIBS thermoplastic elastomer, softener, and 60% antioxidant into a vacuum kneader (NHZ-1L), control the temperature of the vacuum kneader to 170°C, add the first tackifying resin, the second tackifying resin, the bio-type hydrogenated liquid resin, and the remaining antioxidant after mixing evenly, continue to mix evenly and discharge the material after the bubbles are exhausted to obtain a pressure-sensitive adhesive, and perform a performance test on it while hot.

[0175] Embodiment 26

[0176] The difference between Example 26 and Example 19 is that the weight parts of the components are different, as follows:

[0177] 15 parts of SIS thermoplastic elastomer, 20 parts of SIBS thermoplastic elastomer, 14 parts of first tackifying resin, 20 parts of second tackifying resin, 15 parts of bio-type hydrogenated liquid resin, 15 parts of softener, and 1 part of antioxidant 1010.

[0178] Embodiment 27

[0179] The difference between Example 27 and Example 19 is that the weight parts of the components are different, as follows:

[0180] SIS thermoplastic elastomer 25 parts, SIBS thermoplastic elastomer 10 parts, first tackifying resin 19 parts, second tackifying resin 10.5 parts, bio-type hydrogenated liquid resin 25 parts, softener 10 parts, antioxidant 1010 0.5 parts.

[0181] Comparative Example 4

[0182] The only difference between Comparative Example 4 and Example 19 is that no bio-type hydrogenated liquid resin is contained and the weight portion of the softener is 32 parts.

[0183] Comparative Example 5

[0184] The only difference between Comparative Example 5 and Example 19 is that the weight parts of the bio-type hydrogenated liquid resin are 9 parts and the weight parts of the softener are 23 parts.

[0185] Comparative Example 6

[0186] The only difference between Comparative Example 6 and Example 19 is that the weight portion of the bio-based hydrogenated liquid resin is 32 parts and no softener is included.

[0187] The performance test of the pressure sensitive adhesive is carried out as follows. The test results are shown in Table 3.

[0188] The initial adhesion test method in the present invention is "GB / T 31125-2014 Ring initial adhesion test method".

[0189] The peel strength test method in the present invention is "GB / T2792-2014 Test method for peel strength of adhesive tape".

[0190] The test method for the holding force in the present invention is "GB / T 4851-014 Test method for holding force of adhesive tape".

[0191] In the present invention, the glass transition temperature (Tg) is measured by DSC (differential scanning calorimetry).

[0192] Table 4

[0193]

[0194]

[0195] From the above test results, it can be seen that the pressure-sensitive adhesive prepared by separating the bio-type hydrogenated liquid resin obtained by the hydrogenated resin product obtained in this application has good bonding properties. By adding SIS thermoplastic elastomer and SIBS thermoplastic elastomer to the pressure-sensitive adhesive at the same time, the two can synergistically improve the peel strength and low-temperature performance. The comprehensive performance of the pressure-sensitive adhesive can be improved by regulating the amount of each component in the pressure-sensitive adhesive and broadening its application range.

[0196] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing a hydrogenated resin product, characterized in that: The steps include: S1, distilling the ethylene cracking carbon nine fraction to obtain a cracking carbon nine raw material with a distillation range of 150 to 200° C.; S2, mixing the cracked carbon nine raw material with bio-based olefins to obtain a composite; in the composite, the mass fraction (mass fraction) of the cracked carbon nine raw material is greater than or equal to 70% and less than 100%, and the mass fraction of the bio-based olefin is greater than 0 and less than or equal to 30%; S3, subjecting the compound to free radical polymerization to obtain a polymerized resin solution; S4, removing unpolymerized components and oligomers in the polymerized resin liquid to obtain a bio-based carbon nine thermally polymerized petroleum resin; S5, diluting the bio-based carbon nine thermally polymerized petroleum resin with a saturated solvent, filtering, and obtaining a bio-based carbon nine thermally polymerized petroleum resin liquid; S6, performing a hydrogenation reaction on the bio-type carbon nine thermally polymerized petroleum resin liquid to obtain a hydrogenated resin product.

2. The preparation method according to claim 1, characterized in that: The S1 includes at least one of the following features: (1) The distillation method is: adding the ethylene cracking carbon nine fraction into a flash tower, and flashing it under the conditions of a bottom temperature of 150 to 200° C. and a vacuum degree of -0.09 to -0.095 MPa; (2) In the cracking carbon nine raw material, the total mass fraction of naphthalene, methylnaphthalene and dimethylnaphthalene is less than 3%.

3. The preparation method according to claim 1, characterized in that: Includes at least one of the following features: (1) In S2, the bio-based olefin is at least one of α-pinene, β-pinene, limonene, phellandrene, myrcene, cedrene, caryophyllene, longifolene, and santalene; (2) In S2, in the composite, the mass fraction of the cracked carbon nine raw material is greater than or equal to 75% and less than 95%, and the mass fraction of the bio-based olefin is greater than 5 and less than or equal to 25%; (3) In S3, the conditions of the free radical polymerization are: polymerization temperature 200-270° C., polymerization time 10-60 h; (4) In S4, the solvent is removed at 180 to 200° C. and -0.08 to -0.085 MPa, and the oligomer is removed at 200 to 250° C. and -0.09 to -0.095 MPa; (5) In S5, the saturated solvent is at least one of C8-C12 cycloalkanes and C8-C12 straight-chain alkanes; (6) In S5, the mass ratio of the bio-based carbon nine thermally polymerized petroleum resin to the saturated solvent is 1: (8~12)。 4. The preparation method according to any one of claims 1 to 3, characterized in that The S6 includes at least one of the following features: (1) The temperature of the hydrogenation reaction is 200-270°C, the hydrogen pressure is 13-25 MPa, and the space velocity is 0.15-0.55 h -1 , hydrogen-oil ratio is (500-1000):1; (2) The hydrogenation reaction is carried out in a fixed bed hydrogenation reactor, which has four layers, wherein the upper two layers are loaded with a Pd / Ni / C composite catalyst, wherein the Pd / Ni / C composite catalyst is supported by Al2O3; based on the mass fraction of the Pd / Ni / C composite catalyst being 100%, the mass fraction of Pd is 0.5% to 1.5%, the mass fraction of Ni is 8% to 12%, and the molar ratio of C to the Al2O3 is 1:(1 to 2); the specific surface area of ​​the Pd / Ni / C composite catalyst is 70 to 150 m 2 / g, average particle size is 2-6mm, bulk density is 550-750kg / m 3 ; The lower two layers are loaded with Pd / Ni composite catalyst, wherein the Pd / Ni composite catalyst uses Al2O3 as a carrier; taking the mass fraction of the Pd / Ni composite catalyst as 100%, the mass fraction of Pd is 0.5% to 1.5%, and the mass fraction of Ni is 10% to 15%; the specific surface area of ​​the Pd / Ni composite catalyst is 70 to 150 m 2 / g, average particle size is 2-6mm, bulk density is 650-880kg / m 3 .

5. A bio-based hydrogenated carbon nine petroleum resin, characterized in that: Obtained by separating the hydrogenated resin product obtained by the preparation method according to any one of claims 1 to 4; the separation comprises: S1, removing the first solvent in the hydrogenated resin product at 180-200° C. and -0.08--0.085 MPa to obtain a first residual product; S2, cutting the first residual product at 200-250° C. and -0.09-0.095 MPa to obtain hydrogenated oligomers and the bio-based hydrogenated C9 petroleum resin.

6. A hot melt adhesive, characterized in that: The invention comprises the following ingredients in parts by weight: 30 to 50 parts of SIS thermoplastic elastomer, 20 to 40 parts of bio-type hydrogenated carbon nine petroleum resin, 2 to 5 parts of pure aromatic resin, 15 to 25 parts of softener and 0.3 to 1 part of antioxidant; the bio-type hydrogenated carbon nine petroleum resin is the bio-type hydrogenated carbon nine petroleum resin as claimed in claim 5.

7. The hot melt adhesive according to claim 6, characterized in that: Includes at least one of the following features: (1) The SIS thermoplastic elastomer has a linear structure, wherein the mass fraction of styrene is 13% to 17%, and the melt index measured at 200°C and 5kg is 10 to 20g / 10min; (2) The pure aromatic hydrocarbon resin is α-methylstyrene / p-vinyltoluene copolymer resin; (3) The softener is at least one of hydrogenated naphthenic oil, dioctyl phthalate, and paraffin; (4) The antioxidant is at least one of a phosphite antioxidant and a hindered phenol antioxidant.

8. A bio-type hydrogenated liquid resin, characterized in that: Obtained by separating the hydrogenated resin product obtained by the preparation method according to any one of claims 1 to 4; the separation method comprises: S1, removing the first solvent in the hydrogenated resin product at 180-200° C. and -0.08--0.085 MPa to obtain a first residual product; S2, cutting the first residual product at 200 to 250° C. and -0.09 to -0.095 MPa to obtain hydrogenated oligomers and bio-type hydrogenated carbon nine petroleum resin; S3, removing the second solvent in the hydrogenated oligomer at 230-250° C. and -0.09-0.095 MPa to obtain the bio-type hydrogenated liquid resin.

9. A pressure-sensitive adhesive, characterized in that: The invention comprises the following ingredients in parts by weight: 15 to 25 parts of SIS thermoplastic elastomer, 10 to 20 parts of SIBS thermoplastic elastomer, 10 to 20 parts of a first tackifying resin, 10 to 20 parts of a second tackifying resin, 15 to 25 parts of a bio-type hydrogenated liquid resin, 10 to 15 parts of a softener, and 0.3 to 1 part of an antioxidant; the first tackifying resin is a styrene-modified terpene resin, and the second tackifying resin is a maleic anhydride-grafted styrene-modified C5 petroleum resin; the bio-type hydrogenated liquid resin is the bio-type hydrogenated liquid resin according to claim 8.

10. The pressure-sensitive adhesive according to claim 9, characterized in that: Includes at least one of the following features; (1) The SIS thermoplastic elastomer has a linear structure, a styrene mass fraction of 13% to 17%, and a melt index of 10 to 20 g / 10 min measured at 200° C. and 5 kg; (2) The mass fraction of styrene in the SIBS thermoplastic elastomer is 18-21%, and the melt index measured at 200° C. and 5 kg is 10-14 g / 10 min; (3) The softener is at least one of hydrogenated naphthenic oil, dioctyl phthalate, and paraffin; (4) The antioxidant is at least one of a hindered phenol antioxidant and a phosphite antioxidant.